How new generation techniques are shaping the future of environmental sciences - Gruszecka-Kosowska, Agnieszka; Ampatzoglou, Antonios; Pineda-Pampliega, Javier; Mihalache, Octavian Augustin (Frontiers in Environmental Chemistry, 2023)
This perspective highlights the role of new-generation analytical techniques in future applications in environmental sciences since the shift to the One Health research paradigm. It reviews the interactions between the compartments of One Health and indicates the current challenges in traditional environmental research. The term One Health was first used at the beginning of the twentieth century, yet much is still needed for the cross-disciplinary research collaboration required in this approach.